Precision Medicine: Long-Term Treatment with Sulfonylureas in Patients with Neonatal Diabetes Due to KCNJ11 Mutations - Letourneau, Lisa R. (Curr Diab Rep, 2019)
PURPOSE OF REVIEW: The goal of this review is to provide updates on the safety and efficacy of long-term sulfonylurea use in patients with KCNJ11-related diabetes. Publications from 2004 to the present were reviewed with an emphasis on literature since 2014. RECENT FINDINGS: Sulfonylureas, often taken at high doses, have now been utilized effectively in KCNJ11 patients for over 10 years. Mild-moderate hypoglycemia can occur, but in two studies with a combined 975 patient-years on sulfonylureas, no severe hypoglycemic events were reported. Improvements in neurodevelopment and motor function after transition to sulfonylureas continue to be described. SUMMARY: Sulfonylureas continue to be an effective, sustainable, and safe treatment for KCNJ11-related diabetes. Ongoing follow-up of patients in research registries will allow for deeper understanding of the facilitators and barriers to long-term sustainability. Further understanding of the effect of sulfonylurea on long-term neurodevelopmental outcomes, and the potential for adjunctive therapies, is needed.